Percutaneous transhepatic afferent loop balloon dilatation and indwelling catheter placement for benign afferent loop obstruction - Lyo Min Kwon; Myungsu Lee (Society of Gastrointestinal Intervention, 2020)
Benign afferent loop obstruction (ALO) is a complication that occurs after general surgery making Roux-en-Y or Billroth-II reconstruction and has typically been treated surgically. However, the surgery is difficult to conduct in about 25% of cases due to comorbidity and nonoperative management has been attempted. Here, we report two cases of benign ALO that were treated with percutaneous transhepatic afferent loop balloon dilatation and indwelling catheter, including one case with no improvement after surgery.